Answer:
x=0; x=-2
Step-by-step explanation:
so first you do (x+2)^2 which is x^2+2x+4
4x^2 +8x +16 = 16
Subtract 16 from both sides
4x^2 +8x = 0
factor out 4x:
4x(x+2) = 0
Answer:
52.5
Step-by-step explanation:
You divide 35 by 10 and then multiply 15 by that number
Answer:
40% if whats left
Step-by-step explanation:
Answer:
40°
Step-by-step explanation:
It just is
F(1) = 160 is given to us. We'll use it to find f(2)
f(n+1) = -2*f(n)
f(1+1) = -2*f(1) ... replace every n with 1
f(1+1) = -2*160 ... replace f(1) with 160
f(2) = -320
Now use f(2) to find f(3)
f(n+1) = -2*f(n)
f(2+1) = -2*f(2) ... replace every n with 2
f(3) = -2*(-320) ... replace f(2) with -320
f(3) = 640
Finally, use f(3) to find f(4)
f(n+1) = -2*f(n)
f(3+1) = -2*f(3) ... replace every n with 3
f(4) = -2*640 ... replace f(3) with 640
f(4) = -1280
Final Answer: -1280